Intoxication or Sobriety? Examining the Most Famous Example in Islamic Mysticism - Yousefi, Amir; Ashrafimami, Ali (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2024)
The present article examines Bāyazīd Bisṭāmī’s reputation as a mystic of “intoxication” (sukr). The origin and validity of such labels are analyzed by examining their most famous example. It should be noted that for the first time, the author of Kashf al-Maḥjūb labels Bāyazīd as the pioneer of “intoxicated” Ṣūfis. Thus, the main question of this paper is to find out whether Hujwīrī had a correct criterion in his attribution of the ‘Path of Intoxication’ to Bāyazīd or Ibn’ Arabī was right in referring to Bāyazīd’s eminence and fixity (Tamkin). In other words, Hujwīrī introduces Bāyazīd as an intoxicated Ṣūfi, and Ibn’ Arabī calls him as a sober gnostic. To explore our question, we have critically examined Kashf al-Maḥjūb and Hujwīrī’s other reports and have argued that Hujwīrī’s main criterion for attribution of intoxication to Bāyazīd is due to his ecstatic utterances, which is not always an applicable criterion. Moreover, because intoxication and sobriety are not alike and identical, dividing Ṣūfis into two separate sects as ‘intoxicated’ and ‘sober’ is not a precise division. Also, calling a certain sect Ṭayfūriyya can be of Hujwīrī’s own innovation. Then, taking into consideration the words of Ibn’ Arabī about Bāyazīd, we have presented some evidence of Bāyazīd’s sayings and mystical practices to indicate his sobriety.Contribution: This study accurately portrays a renowned Islamic mystic while enhancing the understanding of mystical concepts. It also explores the origins of labeling in Islamic history, illustrating how labels emerge and are subsequently perpetuated by later authors despite inadequate citation or contrary documentation.